Who Rules Over Immunology? Seasonal Variation in Body Temperature, Steroid Hormones, and Immune Variables in a Tegu Lizard. (22nd May 2021) - Madelaire, Carla B; Zena, Lucas A; Dillon, Danielle; Silva, Diego P; Hunt, Kathleen E; Buck, C Loren; Bícego, Kênia C; Gomes, Fernando R
Synopsis: Multiple factors can influence the immune response of ectothermic vertebrates, including body temperature (Tb ), gonadal steroids, and seasonality, in ways that are thought to reflect trade-offs between energetic investment in immunity versus reproduction. Hibernating tegu lizards ( Salvator merianae ) are a unique model to investigate how immunocompetence might be influenced by different factors during their annual cycle. We assessed immunological measures (plasma bacterial killing ability, total and differential leukocyte count), plasma hormone levels (testosterone in males, estradiol and progesterone in females, and corticosterone [CORT] in both sexes), Tb, and body condition from adult tegus during each stage of their annual cycle: reproduction, post-reproduction/preparation for hibernation, and hibernation. Our hypothesis that immune traits present higher values during the reproductive phase, and a sharp decrease during hibernation, was partially supported. Immune variables did not change between life history stages, except for total number of leukocytes, which was higher at the beginning of the reproductive season (September) in both males and females. Average Tb of the week prior to sampling was positively correlated with number of eosinophils, basophils, monocytes, and azurophils, corroborating other studies showing that when animals maintain a high Tb, there is an increase in immune activity. Surprisingly, no clear relationship between immune traits and gonadal steroids or CORT levels was observed, even when including life history stage in the model. When gonadal hormones peaked in males and females, heterophil: lymphocyte ratio (which often elevates during physiological stress) also increased. Additionally, we did not observe any trade-off between reproduction and immunity traits, sex differences in immune traits, or a correlation between body condition and immune response. Our results suggest that variation in patterns of immune response and correlations with body condition and hormone secretion across the year can depend upon the specific hormone and immune trait, and that experienced Tb is an important variable determining immune response in ectotherms.